1984
DOI: 10.1159/000169319
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Complement, Generation of C5a, Leukopenia and Hypoxemia: Interlinked Membrane-Dependent Events during Hemodialysis

Abstract: Differences in biocompatibility of various hemodialysis membranes cause different degrees of complement activation, leukopenia, and hypoxemia during hemodialysis. In order to further clarify the complex sequence of activation of complement, leukopenia and dialysis hypoxemia, we followed leukocyte count and arterial oxygen tension in 23 patients during two successive dialyses using membranes based on regenerated cellulose (RC) and cellulose acetate (CA). In 12 of the patients, signs of complement activation wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 8 publications
2
21
0
Order By: Relevance
“…In addition, the positive correlation observed between C 3 d accumulation and C 5 a desarg suggests that these two indicators of complement activation follow the same 781 kinetics, as also demonstrated by others [36,37], thus reflecting the same in vivo phenomenon. Our results show that complement was related to the neutropenia, but that it participated in a quantitatively different way with each membrane.…”
Section: Haemodialysis-induced Neutropeniasupporting
confidence: 78%
“…In addition, the positive correlation observed between C 3 d accumulation and C 5 a desarg suggests that these two indicators of complement activation follow the same 781 kinetics, as also demonstrated by others [36,37], thus reflecting the same in vivo phenomenon. Our results show that complement was related to the neutropenia, but that it participated in a quantitatively different way with each membrane.…”
Section: Haemodialysis-induced Neutropeniasupporting
confidence: 78%
“…It is rela tively stable and therefore suitable as a marker in clinical studies of complement ac tivation. C3d has been assayed in studies of inflammatory diseases such as systemic lu pus erythematosus [14] and also in evalua tion of the biocompatibility of various de vices used in hemodialysis [6][7][8]. The present results show that estimation of C3d may be a valuable tool also when comparing various procedures of plasma exchange.…”
Section: Discussionmentioning
confidence: 71%
“…In the present study, we measured complement activation in plasma exchange by single filtration and cen trifugation of blood and in cascade filtration. As a parameter, we used C3d formation, which has previously been found to be a use ful marker of complement activation during hemodialysis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Transitory profound leukopenia attends hemodialysis using cellulosic membranes [14], and has been linked to activation of complement and formation of leukocyte aggregatory activity [15], We have previously reported that activation of complement with generation of anaphylatoxin C5a within the dialyzer and dialysis leukopenia are inter linked events, that depend on the type of dia lyzer membrane used [2], The leukopenia is due to a transitory sequestration/embolization of neutrophiles in the pulmonary' vessels as demonstrated both in animals [15] and man [16].…”
Section: Diseussionmentioning
confidence: 99%
“…The pathophysiology of this arterial hypoxemia has not been elucidated in all details, but the composition of the dialysate [1] and the na ture af the dialyzer membrane [2] seem to contribute.…”
Section: Introductionmentioning
confidence: 99%